Improving the Economic Welfare of Members through Productive Loan Services at KSP Kopdit Guru Kelubagolit - Sardiyanto Kedeng Jawa; Henrikus Herdi; Paulus Libu Lamawitak; Thadeus Fransesco Quelmo Patty (International Publisher (YAPENBI), 2024)
This study aims to determine the level of economic welfare of members through productive loan services of KSP Kopdit Kelubagolit. The qualitative data used in this study were obtained through interviews and observations, the qualitative research method is used to research the natural condition of the object. This research focuses on how the internal and external factors of savings and loan cooperatives are managed, namely the management of cooperative institutions and members closely related to MSMEs. This interview was conducted with 1 manager, 1 General Manager, and 3 members of productive borrowers. The results of the study show that activities in the fields of finance, credit, loan surveys, and administrative management support each other to ensure smooth transactions, data accuracy, and transparency in member loan management. Productive loan service mechanism at KSP. Kopdit Guru Kelubagolit is designed to ensure that loans are used effectively in productive activities by evaluating the business feasibility and ability of members, which is also prioritized for members with a history of current loans. Productive loans at KSP. Kopdit Guru Kelubagolit has a significant role in increasing members' income by expanding their business and improving product quality. In addition, it also significantly improves the economic welfare of members through increased income, better expenditure management, increased access to education, health, and better housing.